2021
DOI: 10.3389/fpsyt.2021.695672
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Relapses and Psychosocial Outcomes in Patients With Schizophrenia in Real-World Settings in the United States

Abstract: Aim: To assess associations between relapses and psychosocial outcomes in adult patients with schizophrenia treated in United States (US) healthcare settings.Methods: Data were derived from a point-in-time survey of psychiatrists and their patients with schizophrenia conducted across the US, France, Spain, China, and Japan between July and October 2019. For the purposes of this analysis, only data from US practitioners and patients were included. Disease-specific programmes (DSPs) are large surveys with a vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 37 publications
2
4
0
Order By: Relevance
“…This is explainable by the possibility that multiple admissions may re ect the frequencies of relapses of schizophrenia, where the more the relapses the poor functioning (70). Similar ndings reported in a multinational study involving the United States of America, China, France, Spain, and Japan showing multiple relapses to be associated with functional disability among schizophrenia patients (71). Different results found in a Nigerian study among schizophrenia patients, which showed that there was no difference in odds of functional disability among patients who never admitted and those who had one or more admissions (11).…”
Section: Discussionsupporting
confidence: 64%
“…This is explainable by the possibility that multiple admissions may re ect the frequencies of relapses of schizophrenia, where the more the relapses the poor functioning (70). Similar ndings reported in a multinational study involving the United States of America, China, France, Spain, and Japan showing multiple relapses to be associated with functional disability among schizophrenia patients (71). Different results found in a Nigerian study among schizophrenia patients, which showed that there was no difference in odds of functional disability among patients who never admitted and those who had one or more admissions (11).…”
Section: Discussionsupporting
confidence: 64%
“…This is explainable by the possibility that multiple admissions may re ect the frequencies of relapses of schizophrenia, where more relapses are associated with poor functioning (70). Similar ndings reported in a multinational study involving the United States of America, China, France, Spain, and Japan showing multiple relapses to be associated with functional disability among schizophrenia patients (71). Different results found in a…”
Section: Discussionsupporting
confidence: 51%
“…In a recent survey of psychiatrists and their patients with schizophrenia, patients with fewer relapses in the 12-month span prior to the survey experienced better quality of life, higher levels of employment, fewer symptoms, and greater participation in social interactions. 22 Therefore, careful consideration of adequate treatment before transition between LAI formulations is important for preserving psychosocial functioning and improving clinical outcomes. As longer-acting LAIs, such as PP6M, become available for use, further investigations will be required to determine if a similar stabilization period may be required for optimal post-transition outcomes.…”
Section: Discussionmentioning
confidence: 99%